Struktura skargi mówionej - Wyrwas, Katarzyna (Stylistyka, 2020)
In the article author treats complaint as the most popular way of expressing the negative emotions, as one of speech genres, which exist in every-day human interactions. First the author presents semantic definition of the complaint genre pattern: [I say: I feel badly about Y], This basic structure can be realized in different ways, creating the structurally different texts, so it is necessary to describe linguistic aspects of complaint structure, according to the conception of textual pattern. People recognize the complaints by intuitive identification of most important complaint component: speaker’s discontent. Author present textual pattern of basic structure. It may consist of interjection which express negative emotions (for example Matko Boska!), or it may be just one sentence, which communicates about speaker’s discontent explicite (for example jak mi źle!). Textual pattern of developed structure, composed of sequence of elements, is also presented. Speakers realizes it by giving some informations, for example about person which he is complaining on or about situations which are annoying for him.